A revision of Dichotomius (Homocanthonides) Luederwaldt, 1929 (Coleoptera: Scarabaeidae: Scarabaeinae) - Maldaner,Maria E. (2018)
ABSTRACT The monospecific subgenus Dichotomius (Homocanthonides) is revised and its single species, Dichotomius (H.) smaragdinus (Perty, 1830) is redescribed and distinguished from other Dichotomius species. Dichotomius (H.) smaragdinus is a polymorphic species and its distribution comprises the Brazilian Cerrado. For the first time, morphological variation and male genital organ are described and illustrated. We believe that this species might be endangered due to extensive deforestation of Brazilian Cerrado by agricultural and pasture expansion. Thus, we highlight the importance of preserving this very unusual Dichotomius species.